Proses Produksi Gula Aren Cetak (Arenga pinnata, Merr) Di Indonesia - Hutami, Rosy; Pribadi, Moch Fadlal Islamay; Nurcahali, Fani; Septiani, Bunga; Andarwulan, Nuri; Sapanli, Kastana; Zuhud, Ervizal A. M.; Al Manar, Primadika; Ichsan, Nurul; Wahyudi, Slamet (Jurnal Ilmiah Pangan Halal, 2023)
Palm sap (Arenga pinnata, Merr) is one of the palm plants in Indonesia. Palm sap is the basic ingredient for making palm sugar. Palm sugar processing in Indonesia currently still uses traditional methods so the results and quality are inconsistent, to deal with this, further research is needed on the good tapping process, critical parameters of sap and preservatives used, the process of making palm sugar that is good and correct, and the physicochemical content of sap and palm sugar. The research method used is looking at and returning from several reference journals. The process carried out before wiretapping is pre-tapping or tapping after that the sap-tapping process. Fresh sap has a sweet taste, distinctive aroma of sap, and acidity of pH around 6-7, with sucrose content >12%, and alcohol content < 5%. Sucrose, glucose, fructose and other carbohydrates cause sweetness in sap; generally, palm sap consists of water, protein, fat, and carbohydrates. The critical parameter of palm sap is pH, palm sap that can be processed into palm sugar has a pH of 6 – 7, and palm sap is very critical because of the activity of microbes such as yeast and bacteria so preservatives are needed to maintain its quality, which is often used are natural preservatives such as safat, castor beans, hazelnut seeds, coconut oil, jackfruit stems, guava leaves, and mangosteen peel. The process of making palm sugar is simple: heating sap for 3-5 hours until it thickens and then molded into molds to become palm sugar. The chemical characteristics of palm sugar consist of water content, ash content, reducing sugar content, and sucrose content.